Luminescence properties and energy transfer of La3Ga5SiO14:Eu3+, Tb3+ phosphors. Issue 23 (27th May 2021) - Zuo, Xiang-Gang; Wang, Yi; Wei, Lei; Lv, Xian-Shun; Fu, Yang-Bin; Li, Jing; Zhang, Yuan-Yuan; Wang, Xu-Ping; Liu, Bing; Yang, Yu-Guo
Abstract : The La3 Ga5 SiO14 based phosphors were generated by substitutions of Tb 3+ /Eu 3+ to La 3+ . The Tb 3+ → Eu 3+ energy transfer occurs in Tb 3+ /Eu 3+ codoped phosphors. The La2.70 Eu0.12 Tb0.18 Ga5 Si14 phosphor shows an internal quantum yield about 88.82%. Abstract : In this paper, a series of Eu 3+ /Tb 3+ doped La3 Ga5 SiO14 (LGS:Eu 3+, Tb 3+ ) phosphors with excellent performance have been synthesized by high-temperature solid-phase method. The effects of Eu 3+ and Tb 3+ doping in LGS on the host lattice were analyzed by X-ray diffraction (XRD). X-ray photoelectron spectroscopy (XPS) proved that the Eu 3+ and Tb 3+ ions were successfully doped into the LGS host. The doped Eu 3+ /Tb 3+ ions only occupy the eight-coordinated La 3+ sites. The concentration quenching points of LGS:Eu 3+ and LGS:Tb 3+ phosphors were determined to be 0.16 and 0.18, respectively. The luminescence performance and fluorescence lifetime of LGS:Eu 3+, Tb 3+ were studied. LGS:Eu 3+, Tb 3+ phosphors successfully realized Tb 3+ → Eu 3+ energy transfer to enhance Eu 3+ luminescence. The energy transfer mechanism is speculated on using the experimental results. The energy transfer efficiency from Tb 3+ to Eu 3+ is about 66.83% in La2.46 Tb0.18 Eu0.36 Ga5 SiO14 . The LGS:Eu 3+, Tb 3+ phosphors can achieve tunable luminescence by controlling the doping concentrations of Eu 3+ and Tb 3+ . The Δ E is calculated to be 0.2567 eV for the La2.70 Eu0.12 Tb0.18 Ga5 SiO14 phosphor.